TREX-DM: a low background Micromegas-based TPC for low-mass WIMP detection. Issue 4 (May 2016) - Iguaz, F J; Garza, J G; Aznar, F; Castel, J F; Cebrián, S; Dafni, T; García, J A; Irastorza, I G; Lagraba, A; Luzón, G; Peiró, A
Abstract: Dark Matter experiments are recently focusing their detection techniques in low-mass WIMPs, which requires the use of light elements and low energy threshold. In this context, we describe the TREX-DM experiment, a low background Micromegas-based TPC for low-mass WIMP detection. Its main goal is the operation of an active detection mass 0.3 kg, with an energy threshold below 0.4 keVee and fully built with previously selected radiopure materials. This work describes the commissioning of the actual setup situated in a laboratory on surface and the updates needed for a possible physics run at the Canfranc Underground Laboratory (LSC) in 2016. A preliminary background model of TREX-DM is also presented, based on a Geant4 simulation, the simulation of the detector's response and two discrimination methods: a conservative muon/electron and one based on a neutron source. Based on this background model, TREX-DM could be competitive in the search for low-mass WIMPs. In particular it could be sensitive, e.g., to the low-mass WIMP interpretation of the DAMA/LIBRA and other hints in a conservative scenario.